JEJAK KAKI KARBON PADA INDUSTRI AIR MINUM DALAM KEMASAN - Kusuma, Maritha Nilam (Journal of Research and Technology, 2015)
PT. XYZ is one of industry that has a potential in green house gas emission that produce negative effect on human and environment. Therefore the study was aimed to investigate how much carbon value produced by PT. XYZ and how is the alternative solution to reduce carbon emission.The study method was based on secondary data such as; electricity, water and fuel consumption for one year taken from January until October 2009. The data was analyzed using CWFP, SEI, and ACM0002 methods for carbon emission value. The solution alternative for reducing carbon emission of PT. XYZ, was compared between electricity, natural gas and coal. It was concluded that, emission carbon value of PT. XYZ is 6.966,69 Tonnes CO2/years. Keywords: carbon emission, emission factor, and bottled water industry.